2021
DOI: 10.1002/adma.202006946
|View full text |Cite
|
Sign up to set email alerts
|

Growing Living Composites with Ordered Microstructures and Exceptional Mechanical Properties

Abstract: Living creatures are continuous sources of inspiration for designing synthetic materials. However, living creatures are typically different from synthetic materials because the former consist of living cells to support their growth and regeneration. Although natural systems can grow materials with sophisticated microstructures, how to harness living cells to grow materials with predesigned microstructures in engineering systems remains largely elusive. Here, an attempt to exploit living bacteria and 3D‐printed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…In nature, living organisms are experts in engineering hierarchical structures of organic‐inorganic composites through biomineralization, endowing the biological materials with unique biomechanical and biophysical functions. [ 1–3 ] Inspired by natural design, recent development in functional composites has enabled incorporation of living ingredients (i.e., cells, bacteria, and spores) within material composites, [ 4–7 ] imparting these structures with living attributes, such as response to external stimuli, catalytic activity, metabolic activity, adaptability, and self‐growing. [ 2,8 ] Specifically, biomimetic mineralization has generated composite structures that resemble or even outperform their natural counterparts, where non‐living polymer backbones (i.e., synthetic polymers, polysaccharides, and proteins) are used as scaffolds for biomineralization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, living organisms are experts in engineering hierarchical structures of organic‐inorganic composites through biomineralization, endowing the biological materials with unique biomechanical and biophysical functions. [ 1–3 ] Inspired by natural design, recent development in functional composites has enabled incorporation of living ingredients (i.e., cells, bacteria, and spores) within material composites, [ 4–7 ] imparting these structures with living attributes, such as response to external stimuli, catalytic activity, metabolic activity, adaptability, and self‐growing. [ 2,8 ] Specifically, biomimetic mineralization has generated composite structures that resemble or even outperform their natural counterparts, where non‐living polymer backbones (i.e., synthetic polymers, polysaccharides, and proteins) are used as scaffolds for biomineralization.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,8 ] Specifically, biomimetic mineralization has generated composite structures that resemble or even outperform their natural counterparts, where non‐living polymer backbones (i.e., synthetic polymers, polysaccharides, and proteins) are used as scaffolds for biomineralization. [ 1,9 ] Living microorganisms, such as bacteria, [ 5,7,10 ] embryonic primary mesenchyme cells, [ 11 ] microalgae, [ 12 ] fungal cells, [ 13,14 ] chloroplasts, [ 15 ] and lysozyme, [ 16,17 ] have been harnessed to produce minerals in a spatiotemporally‐patterned manner. These 3D printed architectures with microorganism‐assisted mineralization could not only mimic the highly‐organized and time‐evolving biological structures, but also enable their new utilities as functional materials and devices.…”
Section: Introductionmentioning
confidence: 99%
“…These engineered living materials possess multiple advantages including capable of generating biologics responding to local environment and yielding more adaptations through autonomously biological behaviors [2] . At present, bacteria, fungi and stem cells have been used in living materials for a range of applications such as biosensing, tissue regeneration and drug delivery [3,4] . Living materials exhibit "living character" through living cells on polymeric matrice blocks constructing bioactive and bioresponsive units [5] .…”
mentioning
confidence: 99%
“…[28] In the direct writing process, the conductive particles in printable ink tend to rotate and orientate with the assistance of the shear force, especially referring to short high-aspectratio fibers. [22,[29][30][31][32][33][34][35][36] The oriented fillers guarantee the printed composites with anisotropic properties and the 3D process enables a high freedom in control of the orientation, and the printed ordered microstructures have been applied as bionic composites. [24,36] The anisotropic composites as sensors have only been primarily explored.…”
mentioning
confidence: 99%
“…[22,[29][30][31][32][33][34][35][36] The oriented fillers guarantee the printed composites with anisotropic properties and the 3D process enables a high freedom in control of the orientation, and the printed ordered microstructures have been applied as bionic composites. [24,36] The anisotropic composites as sensors have only been primarily explored. Zhang et al [37] recently reported anisotropic strain sensors with periodically wrinkled structures, where the anisotropic electromechanical behaviors are applied in detecting complex multidimensional strains.…”
mentioning
confidence: 99%